2013
DOI: 10.5937/industrija41-4024
|View full text |Cite
|
Sign up to set email alerts
|

Corporate bankruptcy prediction in the Republic of Serbia

Abstract: The aim of this paper is to present corporate default prediction models constructed in the specific market conditions that prevail in the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…The aim was to use predictors that originate from the period of two years, maximum, before the year for which the forecast is made so that the applicability of the models is magnified. The Altman's Z"-score model was chosen as the foundation for building the models because it is a well-known model for assessing bankruptcy risk and it has confirmed applicability in the economic environment of the Republic of Serbia [1,120,121,123]. It is also the only model that has previously been used to investigate the bankruptcy risk in the hotel industry in the Republic of Serbia [30,123], and so the comparability with these studies is ensured.…”
Section: Methodology Of the Researchmentioning
confidence: 99%
“…The aim was to use predictors that originate from the period of two years, maximum, before the year for which the forecast is made so that the applicability of the models is magnified. The Altman's Z"-score model was chosen as the foundation for building the models because it is a well-known model for assessing bankruptcy risk and it has confirmed applicability in the economic environment of the Republic of Serbia [1,120,121,123]. It is also the only model that has previously been used to investigate the bankruptcy risk in the hotel industry in the Republic of Serbia [30,123], and so the comparability with these studies is ensured.…”
Section: Methodology Of the Researchmentioning
confidence: 99%
“…Rajin et al showed that Kralicek's DF model more effectively indicates the financial state of the company than Altman's Z-score model, considering the characteristics of the market in which the model is formed [73]. Because the number of bankrupt companies in the Republic of Serbia has significantly increased, it is particularly important to emphasize the need to apply a model suitable for emerging economies [74].…”
Section: Predicting Bankruptcy Using Altman's Z-score Model and Determining The Possibility Of Fraudulent Financial Reporting Using The Bmentioning
confidence: 99%